Woman to woman: an everywoman's guide to lesbian sexuality - Booth, Carol (Simon & Schuster, 2002)
Section: 288 pages : illustrations ; 22 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

L'engendrement des choses: des hommes, des femmes et des techniques - Chabaud-Rychter, Danielle; Gardey, Delphine (EAC, 2002)
"Le monde contemporain est marqué par une amplification des biens et des choses, des techniques et des artefacts ; toutes choses nous semblant à la fois ordinaires, évidentes et neutres. Cette modernité est rarement interrogée du point de vue des hommes et des femmes qui la vivent. Pourquoi en effet prêter des intentions aux choses? Elles participent de nos vies, pourvoient à nos besoins, nous soulagent de bien des tâches. Remettre en question la neutralité des techniques est pourtant une bonne façon de s'interroger sur les rapports sociaux de sexes, en se demandant pourquoi les femmes sont durablement exclues de certains domaines techniques ; quel pouvoir confère la maîtrise des techniques ; quel est l'enjeu politique et symbolique de cette maîtrise ; et, au bout du compte, comment les techniques contribuent à ordonner le social, et en particulier les relations sexuées."
Section: 328 p. : ill. ; 22 cm.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

L'économie sociale du point de vue des femmes - Corbeil, Christine; Descarries, Francine; Galerand, Elsa (LAREPPS, 2002)
Actes du colloque
https://www.socioeco.org/bdf_fiche-document-5338_fr.html
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; discipline; division sexuelle du travail; périodes historiques; québec; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; travail; économie; économie sociale

Climate change vulnerability, impacts, and adaptation: Why does gender matter? - Denton, Fatma (Gender & Development, 2002)
Gender-related inequalities are pervasive in the developing world. Although women account for almost 80 per cent of the agricultural sector in Africa, they remain vulnerable and poor. Seventy per cent of the 1.3 billion people in the developing world living below the threshold of poverty are women. It is important that the consequences of climate change should not lead already marginalised sections of communities into further deprivation. But key development issues have been at best sidetracked, and at worst blatantly omitted, from policy debates on climate change. The threats posed by global warming have failed to impress on policy-makers the importance of placing women at the heart of their vision of sustainable development. This article argues that if climate change policy is about ensuring a sustainable future by combining development and environment issues, it must take into account the interests of all stakeholders. The Global Environment Facility and the Clean Development Mechanism of the Kyoto Protocol can play a role in ensuring sustainable development, provided they are implemented in a way that does not disadvantage women and the poor.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; changements climatiques; discipline; environnement; projet charge mentale; périodes historiques; santé; science politique; science politique et droit; thématiques

La résistance à la pénalité : un impératif féministe - Faith, Karlene (Criminologie, 2002)
À l’ère de la croissance galopante des prisons sous forme de complexe industriel en Amérique du Nord, les tensions idéologiques vacillent entre châtiment et mouvements en faveur d’une justice réparatrice ou transformatrice. Entre les désinstitutionnalistes, qui cherchent à réduire le nombre de personnes en prison, et les abolitionnistes pénaux, qui visent une transformation sociale, on retrouve nombre de féministes canadiennes. Les femmes au Canada sont désillusionnées suite à l’échec du gouvernement fédéral à mettre en pratique la vision de La création de choix, un rapport d’un groupe de travail sur l’emprisonnement des femmes, datant de 1990. Le gouvernement n’a pas non plus tenu compte des importantes recommandations de la juge Louise Arbour, dont l’enquête de 1996 sur les inconduites du personnel correctionnel met en lumière le non-respect des lois dans les prisons. En 2002, encore plus de femmes se retrouvent dans les prisons à sécurité moyenne ou maximale au Canada pour des crimes relativement mineurs. Les années 1990 nous ont fourni une bonne leçon sur la futilité de la réforme des prisons, tout spécialement au nom du féminisme. Dans l’avenir, les féministes devront impérativement contester les fondements de la pénalité imposée par l’État plutôt que de tenter de réformer une institution désuète.
https://id.erudit.org/iderudit/008293ar
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; canada; criminologie; discipline; femmes* en prison; histoire et politique; justice sociale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; thématiques

Unequal freedom: how race and gender shaped American citizenship and labor - Glenn, Evelyn Nakano (Harvard University Press, 2002)
The inequalities that persist in America have deep historical roots. Evelyn Nakano Glenn untangles this complex history in a unique comparative regional study from the end of Reconstruction to the eve of World War II. During this era the country experienced enormous social and economic changes with the abolition of slavery, rapid territorial expansion, and massive immigration, and struggled over the meaning of free labor and the essence of citizenship as people who previously had been excluded sought the promise of economic freedom and full political rights.After a lucid overview of the concepts of the free worker and the independent citizen at the national level, Glenn vividly details how race and gender issues framed the struggle over labor and citizenship rights at the local level between blacks and whites in the South, Mexicans and Anglos in the Southwest, and Asians and haoles (the white planter class) in Hawaii. She illuminates the complex interplay of local and national forces in American society and provides a dynamic view of how labor and citizenship were defined, enforced, and contested in a formative era for white-nonwhite relations in America.
Le chapitre « Citizenship: Universalism and Exclusion » a été donné en lecture au cours POL4212.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amériques; approches et analyses; cours; discipline; droits des femmes*; droits des personnes; histoire et politique; intersectionnalité; inégalités; pol4212; premier cycle; périodes historiques; racisme; racisme systémique; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis; études critiques de la race; études de genres

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

Enjeux contemporains du féminisme indien - Haase-Dubosc, Danielle (Éditions de la Maison des sciences de l'homme, 2002)
Pour la première fois en français, un recueil d'essais témoigne des luttes et de la politique féministes en Inde, dans un contexte bien différent des problématiques occidentales. Inscrits dans la période contemporaine, de la turbulence des années 1960 et 1970 aux défis des années 1990, certains de ces textes ont été rédigés à chaud, d'autres sont plus rétrospectifs. Ils constituent un ensemble original à travers six grandes rubriques qui se complètent et se répondent l'une l'autre ... Tout en présentant les expériences historiques particulières qui ont nourri les théories et les pratiques du mouvement des femmes en Inde, cet ouvrage présente une approche vivante et engagée des questions actuellement en jeu pour les femmes indiennes.une vision plurielle du féminisme , dans une perspective transnationale respectueuse de l'altérité historique et culturelle
Keywords: 1900-1999; 1960-1969; 1970-1979; approches et analyses; asie; conflit; cours; cycles supérieurs; droits des femmes*; fem1000; fem7000; histoire des femmes*; histoire et politique; inde; inégalités; lit3220; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques

Femmes, violences et espace public: une réflexion sur les politiques de sécurité - Lieber, Marylène (Lien social et Politiques, 2002)
Lorsqu'on se penche sur les politiques publiques concernant les violences en France, on relève une division des compétences entre les politiques dites « de sécurité » et les politiques « contre les violences faites aux femmes ». On constate que les politiques de sécurité, en se basant sur les statistiques de criminalité et de victimation, portent essentiellement sur l'espace public et marginalisent les violences faites aux femmes dans l'espace privé. Pour autant, elles ne prennent pas non plus en considération les violences perpétrées à leur encontre dans l'espace public. Or, divers exemples venant de pays étrangers esquissent des réponses faites par les pouvoirs publics à ces violences
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; pol4102; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; sécurité; thématiques; violences

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

La "conscientisation" dans le militantisme des années 1970 - Mathieu, Lilian (Discours savants, discours militants: mélange des genres, 2002)
"OGM, nucléaire, principe de précaution, comité de sages, experts… autant de figures ou de domaines pour lesquels science et politique sont étroitement imbriquées. Le recours dans le débat public à la science et à l'expertise semble constituer une ressource politique susceptible de convaincre efficacement. Les auteurs montrent la diversité des usages militants des discours savants et saisissent les conditions de " passage " des discours d'un univers à l'autre."– Site de l'éditeur.
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; justice sociale; militance; pédagogie; périodes historiques; ressource en ligne; science politique; science politique et droit; thématiques

Gender and the silences of social capital: Lessons from Latin America - Molyneux, Maxine (Development and Change, 2002)
Social capital has entered development policy thinking and practice in Latin America where it converges with the premises of a new development agenda that emerged in the 1990s. Women are often central to the forms of social capital that development agencies are keen to mobilize in poverty relief programmes, but the terms of women’s insertion into these programmes is rarely problematized. This article critically examines the gendered assumptions that govern efforts to build social capital, and explores some of the tensions that have arisen in post-transition Latin America between women’s rights and social capital agendas.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique latine; amériques; approches et analyses; discipline; droits des femmes*; inégalités; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques

The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis

La violence nazie, une généalogie européenne - Traverso, Enzo (La Fabrique, 2002)
La violence nazie ne doit rien au hasard: elle a une généalogie, qui n'est pas spécifiquement allemande, et un laboratoire, l'Europe libérale du XIXe siècle.Les camps d'extermination sont l'aboutissement d'un long processus de déshumanisation et d'industrialisation de la mort, amorcé par la guillotine et qui a progressivement intégré la rationalité du monde moderne, celle de l'usine, de la bureaucratie, de la prison. On peut trouver les origines culturelles du nazisme dans le "racisme de classe" qui triomphe après la Commune, dans le discours impérialiste sur l'"extinction des races inférieures" visant à légitimer les génocides coloniaux, enfin dans l'émergence d'une nouvelle image du juif- axée sur la figure de l'intellectuel - comme métaphore d'une maladie du corps social.Le nazisme réalisera la convergence entre ces différentes sources matérielles et idéologiques. Auschwitz se révèle ainsi - et c'est là que réside, selon Enzo Traverso, sa singularité - comme la synthèse d'un ensemble de modes de pensée, de domination et d'extermination profondément inscrits dans l'histoire occidentale.
disponible en ligne : https://shs-cairn-info.proxy.bibliotheques.uqam.ca/la-violence-nazie–9782913372146?lang=fr donné en lecture au cours POL5480, p.44-91.
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; approches et analyses; cours; discipline; europe; histoire; histoire et politique; pol5480; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences